A Cross-Sectional Factor Analysis of COVID-19 and Influenza Vaccination Decisions in a Racially Diverse Western Pennsylvania Community - Jorna Sojati; Anjana Murali; Catherine Pressimone; Allie Dakroub (SAGE Publishing, 2023)
Introduction: Influenza and COVID-19 vaccination rates remain suboptimal, demanding new community-centric approaches that improve targeted counseling and increase vaccine uptake. Notably, racially diverse communities show high vaccine hesitancy, yet most existing vaccine studies focus on white, college-educated cohorts. Objective: Here, we identify factors influencing vaccination decisions of patients at Turtle Creek Primary Care clinic in Turtle Creek, PA, a racially-diverse borough. Design: A retrospective mixed-methods study of the predominantly non-white patient population at Turtle Creek Primary Care clinic, a clinic caring for >70% minority patients. Results: Fourteen factors emerged that patients reported were crucial to vaccine decision-making. Of these factors, top reasons for COVID-19 vaccine hesitancy were trust in vaccines, vaccine side effects, perceived vaccine knowledge, and faith/religion. Top reasons for influenza vaccine hesitancy were perceived need, vaccine side effects, trust in vaccines, and habitual behaviors. We also uncovered correlations between vaccine decision factors and sociodemographic factors. Participants > 65-years-old were more likely to cite personal safety in choosing to get the COVID-19 vaccine, while non-white participants were more likely to cite others' safety. Participants > 65-years-old were also more likely to cite personal safety in influenza vaccine decision-making, and non-female participants were more likely to cite perceived need for influenza vaccines. Conclusions: These data uncover targetable factors contributing to vaccine hesitancy and aid in developing community-centered, personalized vaccine education approaches in Turtle Creek and analogous minority communities.